Feynman amplitudes, periods and motives : international research workshop, periods and motives - a modern perspective on renormalization, July 2-6, 2012, Instituto de Ciencias Matemáticas, Madrid, Spain - Periods and Motives (Workshop); Álvarez-Cónsul, Luis; Burgos Gil, José Ignacio; Ebrahimi-Fard, Kurusch (Contemporary mathematics, 2015)
This volume contains the proceedings of the International Research Workshop on Periods and Motives--A Modern Perspective on Renormalization, held from July 2-6, 2012, at the Instituto de Ciencias Matematicas, Madrid, Spain.Feynman amplitudes are integrals attached to Feynman diagrams by means of Feynman rules. They form a central part of perturbative quantum field theory, where they appear as coefficients of power series expansions of probability amplitudes for physical processes. The efficient computation of Feynman amplitudes is pivotal for theoretical predictions in particle physics.Periods are numbers computed as integrals of algebraic differential forms over topological cycles on algebraic varieties. The term originated from the period of a periodic elliptic function, which can be computed as an elliptic integral.Motives emerged from Grothendieck's ``universal cohomology theory'', where they describe an intermediate step between algebraic varieties and their linear invariants (cohomology). The theory of motives provides a conceptual framework for the study of periods. In recent work, a beautiful relation between Feynman amplitudes, motives and periods has emerged.The articles provide an exciting panoramic view on recent developments in this fascinating and fruitful interaction between pure mathematics and modern theoretical physics.